The genome and microbiome of a dikaryotic fungus (Inocybe terrigena, Inocybaceae) revealed by metagenomics. Issue 2 (2nd February 2018) - Bahram, Mohammad; Vanderpool, Dan; Pent, Mari; Hiltunen, Markus; Ryberg, Martin
Summary: Recent advances in molecular methods have increased our understanding of various fungal symbioses. However, little is known about genomic and microbiome features of most uncultured symbiotic fungal clades. Here, we analysed the genome and microbiome of Inocybaceae (Agaricales, Basidiomycota), a largely uncultured ectomycorrhizal clade known to form symbiotic associations with a wide variety of plant species. We used metagenomic sequencing and assembly of dikaryotic fruiting‐body tissues from Inocybe terrigena (Fr.) Kuyper, to classify fungal and bacterial genomic sequences, and obtained a nearly complete fungal genome containing 93% of core eukaryotic genes. Comparative genomics reveals that I. terrigena is more similar to ectomycorrhizal and brown rot fungi than to white rot fungi. The reduction in lignin degradation capacity has been independent from and significantly faster than in closely related ectomycorrhizal clades supporting that ectomycorrhizal symbiosis evolved independently in Inocybe . The microbiome of I. terrigena fruiting‐bodies includes bacteria with known symbiotic functions in other fungal and non‐fungal host environments, suggesting potential symbiotic functions of these bacteria in fungal tissues regardless of habitat conditions. Our study demonstrates the usefulness of direct metagenomics analysis of fruiting‐body tissues for characterizing fungal genomes and microbiome.